Upaya meningkatkan hasil belajar PKn pada materi menjaga keutuhan nkri melalui metode bermain peran dengan pendekatan cooperative learning pada siswa kelas v sekolah dasar - Sunarti Sunarti (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
This research is a classroom action research (PTK) with the research subjects being the fifth grade students of SD Negeri 1 Bulurejo Juwiring Klaten in the 2018/2019 academic year. The data collection methods used in this research are test, interview and observation methods. The collected data were analyzed using descriptive analysis. Based on the data analysis, it can be concluded that: 1) Through the role-playing method with the cooperative learning approach, it can increase PKN learning activities to maintain the integrity of the Republic of Indonesia in grade V SD Negeri 1 Bulurejo Juwiring Klaten in the 2018/2019 academic year. This can be seen from the average activity in cycle I which reached 57.09% and increased to 76.4% in cycle II; 2) Through the role-playing method with a cooperative learning approach,  it can improve PKN learning activities to maintain the integrity of the Republic of Indonesia in class V SD Negeri 1 Bulurejo Juwiring Klaten in the 2018/2019 academic year. This can be shown by the increase in: (1) The average value in the pre-research study obtained a class average of 66 with 28.57% completeness in learning, (2) in the first cycle the average grade was 75 with learning completeness 71.4 %, (3) and in the second cycle the class average was 82.53 with 89.28% learning completeness. This shows that the student learning outcomes of Civics achieved the mastery target of> 85% with a KKM value> 70.